2022
DOI: 10.1111/hel.12873
|View full text |Cite
|
Sign up to set email alerts
|

Need for standardization and harmonization of Helicobacter pylori antimicrobial susceptibility testing

Abstract: Background and aims As with other infectious diseases, Helicobacter pylori eradication regimens should be guided by susceptibility testing to achieve excellent success rate, especially in the era of high antibiotic resistance. However, susceptibility testing for H. pylori is rarely performed, which can be partly ascribed to the current lack of standardization of testing methods and the lack of unified consensus on the antibiotic resistance breakpoints. The aim of this review was to call for an international co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 73 publications
0
9
0
2
Order By: Relevance
“…Probiotics, in conjunction with recommended therapies, slightly increased the eradication rate and significantly decreased the adverse effects of antibiotics [46]. Susceptibility testing may guide the selection of the most effective treatment regimens and improve the eradication rate to exceed 90% [47]. It has been suggested that amoxicillin, clarithromycin, levofloxacin, and metronidazole should be routinely evaluated for H. pylori susceptibility [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, in conjunction with recommended therapies, slightly increased the eradication rate and significantly decreased the adverse effects of antibiotics [46]. Susceptibility testing may guide the selection of the most effective treatment regimens and improve the eradication rate to exceed 90% [47]. It has been suggested that amoxicillin, clarithromycin, levofloxacin, and metronidazole should be routinely evaluated for H. pylori susceptibility [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic methods take at least 1–2 weeks to grow the fastidious microaerophilic bacterium 45 . Compared with the phenotypic method, the time cost of genotype testing of stool samples is very low, which ensures a shorter interval from diagnosis to upcoming individualized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic methods take at least 1-2 weeks to grow the fastidious microaerophilic bacterium. 45 Compared with the phenotypic method, the time cost of genotype testing of stool samples is very low, which ensures a shorter interval from diagnosis to upcoming individualized treatment. Regarding the time interval to obtain resistance results, nested PCR takes 6.5 h from extraction to completing analysis; Genotype HelicoDR analysis 5 h; Amplidiag to the heterogeneity of the pooled sensitivity.…”
Section: Eradication Therapy Of H Pylori Infection Based On the Clari...mentioning
confidence: 99%
“…However, few antibiotics have been developed successfully ( Tacconelli et al, 2018 ). Antimicrobial susceptibility testing for H. pylori is rarely performed partly due to the lack of standardized testing methods and consensus on antibiotic resistance breakpoints ( Li et al, 2022 ). The salvage therapy may be selected empirically after first-line therapy fails ( Chey et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%